An in depth analysis of neural network with application in finance - Tasnim, Noshin; Yasmeen, Farhana (BRAC University, 2019)
This thesis is submitted in partial fulfillment of the requirements for the degree of Bachelor of Science in Computer Science and Engineering, 2019.